Multiple Cavitary Nodules Accompanied by Pulmonary Nocardiosis in a Patient with Systemic Lupus Erythematosus - Zehra Çağla KARAKOÇ; Şule NAMLI; Süleyman Tevfik ECDER; Recep TEKİN4 (Archives of Rheumatology, 2011)
Pulmonary nocardiosis is a chronic suppurative infection that may occur in immunosuppressed patients. It can be self-limited, or it can have an acute, subacute, or chronic course. Radiological diagnosis of pulmonary nocardiosis is difficult because of the very low prevalence of the disease even in immunocompromised patients and is also problematic because the radiographic findings are diverse with no characteristic findings. Multiple nodules and cavitations are more commonly described in acquired immune deficiency syndrome (AIDS) patients but are uncommon in non-AIDS patients. Also, the association of nocardia infection with systemic lupus erythematosus has been described occasionally. In this article, we report a rare case of pulmonary nocardiosis with multiple cavitary lesions and acute respiratory failure in a HIV-negative patient with systemic lupus erythematosus who was receiving corticosteroid treatment.